2018
DOI: 10.1002/anie.201803246
|View full text |Cite
|
Sign up to set email alerts
|

Two Amphoteric Silver Carbene Clusters

Abstract: Two highly labile silver carbene cluster complexes are described, which are unique in that they mark the transition point at which the carbene center transmutes from a fairly common NHC‐like nucleophilic behavior to an electrophilic character befitting reactive silver carbene intermediates of relevance in various catalytic transformations. This amphoteric character is the distinguishing attribute of a μ‐bridged donor/donor carbene entity that connects two silver atoms of triangular or tetrahedral metallic core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…These data suggest that difluorocarbene complexes of type A are likely at the edge of being observable. [22] This supposition is in line with aprevious study which showed that treatment of compound 6 with BF 3 ·Et 2 Os olely afforded the carbonyl complex 8 (Scheme 1). [23] Thet ransient gold difluoro-carbene species 7,a st he likely intermediate of this reaction, could not be detected by 19 FNMR at À80 8 8C; hydrolysis must be extremely fast even under such notably mild conditions.…”
supporting
confidence: 72%
“…These data suggest that difluorocarbene complexes of type A are likely at the edge of being observable. [22] This supposition is in line with aprevious study which showed that treatment of compound 6 with BF 3 ·Et 2 Os olely afforded the carbonyl complex 8 (Scheme 1). [23] Thet ransient gold difluoro-carbene species 7,a st he likely intermediate of this reaction, could not be detected by 19 FNMR at À80 8 8C; hydrolysis must be extremely fast even under such notably mild conditions.…”
supporting
confidence: 72%
“…It is important to recognize, however, that this terminology denotes only the extremes of a continuum: it is not necessarily intuitive by looking at the molecular structure to which category a given metal carbene complex may belong. The famous Grubbs catalysts, which have revolutionized the practice of olefin metathesis, may perhaps be cited in this context …”
Section: Methodsmentioning
confidence: 99%
“…Thef amous Grubbs catalysts,w hich have revolutionized the practice of olefin metathesis,may perhaps be cited in this context. [6][7][8][9][10] Pianostool ruthenium complexes of type D are isoelectronic with Grubbs carbenes.Although such species had been invoked as reactive intermediates in an umber of different transformations including cyclopropanation, [11,12] little was known about structure and bonding until very recently.O ur current interest was invigorated by the finding that carbenes of this type can be generated by gem-hydrogenation of ordinary alkynes using [Cp*RuCl] 4 as the catalyst. [13,14] This unorthodox transformation, in which both H-atoms of H 2 are delivered to one and the same C-atom of the triple bond, has no precedent in the classical canon of homogeneous catalysis; it constitutes the early phase of areaction pathway that allows alkynes to be converted into E-alkenes H by trans-selective semi-reduction (Scheme 1).…”
mentioning
confidence: 99%